Natural abundance of Sb and Sc in pristine groundwaters, Springwater Township, Ontario, Canada, and implications for tracing contamination from landfill leachates - Shotyk, William; Krachler, Michael; Chen, Bin; Zheng, Jiancheng (Journal of environmental monitoring, 2005)
Using ICP-SMS and the clean lab methods and procedures developed for determining trace element concentrations in polar snow and ice, a lower limit of detection (LOD) of 30 pg l−1 for Sb and 5 pg l−1 for Sc was achieved, allowing the natural abundances of Sb and Sc to be measured in pristine groundwaters. Water samples were collected from natural flows and wells between Elmvale and Wyevale in Springwater Township, Ontario, Canada. The water in this region is derived from chemical reactions between meteoric fluids and the Quaternary sediments which cover the bedrock (dolomitic limestone) to depths of more than 100 m. The chemical composition of these waters (pH 8) is primarily a reflection of reactions between the percolating fluids with calcite and dolomite. The maximum concentration of Sb was 5.0 ng l−1, and the average of all samples collected was 2.2 ± 1.2 ng l−1 (n = 34). The average concentration of Sc was 8.6 ± 4.7 ng l−1 (n = 28). The paucity of published Sb concentration data available for comparison is probably because most of the analytical methods commonly used to date, including GFAAS, HG-AAS, HG-AFS, INAA, and ICP-QMS, have lower limits of detection which are inadequate for reliably determining the natural abundance of Sb in many uncontaminated groundwaters. Also, the measurement of extremely low concentrations of Sb requires extra care to avoid possible contamination. Given the extensive use of Sb in plastics, we show that some of the containers used to collect and store samples, and for handling and preparing samples for chemical analyses, may be important sources of contamination in the laboratory. The Sb and Sc concentrations reported here should serve as reference values for this region, against which contamination by various human impacts in future could be compared.
Gesehen am 29.09.2020